M‐ary differential chaos shift keying with carrier index modulation for high‐data‐rate transmission - Bin Yu; Guo‐Ping Jiang; Hua Yang; Ya‐Qiong Jia (IET Communications)
Abstract A high‐data‐rate solution for M‐ary differential chaos shift keying (MDCSK) based on carrier index modulation is proposed in this paper. At the transmitter, the proposed system employs index selectors, Hilbert transform, and MDCSK encoders. Walsh codes are used for separating different data‐bearing wavelets. At the receiver, the proposed system adopts energy comparators and MDCSK detectors. The transmitted chaotic signals are duplicated for several times, and the averaging operation is performed on received signals to reduce noise. Theoretical bit error rate expressions are obtained over the AWGN and the multipath Rayleigh fading channels, respectively. Simulations and comparisons are performed to verify the effectiveness of the proposed scheme.